Development of a groundwater contamination index based on the agricultural hazard and aquifer vulnerability: Application to Portugal - Serra, João (2021)
Reducing nitrate leachingmay not result in a significant improvement of groundwater quality. The amount of nitrate reaching groundwater depends not only on the hazard related to agricultural activities but also on-site specific groundwater vulnerability. Using national databases and other compiled datasets, the agricultural hazard was calculated as the ratio of (i) the nitrate leached estimated from the N surplus, and (ii) the water surplus, a proxy of the percolatingwater belowthe root zone. By combining the hazardwith a multi-parameter groundwater vulnerability, a spatially explicit groundwater contamination risk, developed for mainland Portugal,was computed for 1999 and 2009. Results showan increase from8,800 to 82,679 ha of the territory ratedwith a very high contamination risk. The priority areas were successfully screened by the Index, coinciding with the current Vulnerable Zones, although additional hotspots were detected in southern Portugal. Percolation, including both irrigation activity and precipitation, was found to be a key driver for the groundwater contamination risk due to its opposite effects in the hazard and in the vulnerability. Reducing nitrogen leaching may be insufficient to reduce the risk of nitrate contamination if there is a relatively larger reduction in precipitation. This index is particularly useful when applied to contrasting situations of vulnerability and hazard,which require distinct mitigation measures to mitigate groundwater contamination